Um sistema de recomendações e estatísticas a partir de um prontuário eletrônico odontológico - Toffolo, Geferson (2018)
Currently, the technological advance has supported the development of many companies, helping the work of the managers. The Technology, when applied in the health area, plays an important role in the management of patient data. However, when applied on efficient and correct way, it has contributed significantly to improving people’s quality of life. In this context, the electronic patient’s records become an important tool in the gathering of data pertinent to dentistry. This research has like main objective the generation of diagnostic recommendations and statistical graphics through an dental electronic medical record in the web modality. For achieving the results was developed an electronic patient record having like a reference base the Dentistry College of Passo Fundo University. For the results generate analyzes and knowledge for scientific publications, was incorporated a system of recommendations for diagnostics and generation of statistical graphics. To verification the effectiveness of the referral system, 395 electronic records were used. The results indicated that it was efficient to present a confidence level of 93.3%. The usability evaluation of the system reached the average of 71.7. It was composed of 10 questions adapted from the SUS method. The results for the statistical graphs were extracted through the application of five questions, obtaining an average score of 4.3 on a scale of 0 to 5. Considering the three evaluations, checked an alignment with the objectives of the proposed research.